Sustainable pedestrian routing within UMP Gambang - Nur Nadiah, Burhanuddin (2017)
In order to encourage university in becoming a with world-class technology university, some improvement must be done within campus especially the walkways, by introducing sustainable routing within campus. The main reasons why this research focusing on the walkways are to provide convenience walkway passage for the campus community to walk and encourage further use of non-motorized transportation within the campus as well as making UMP Gambang as a sustainable campus. A sustainable campus integrated green elements and nature to provide healthy environment as well as spaces that support social integration among the community. The objectives of the study are to identify popular origin – destination of community within UMP Gambang, to identify the demand of walkway users within UMP Gambang and to identify the requirement needed by community for routes sustainability in UMP Gambang. 1000 set of questionnaires were distributed to 1000 respondents from UMP communities to get their respond and opinions. The questionnaire survey parameters include personal details of respondents within UMP Campus Gambang, the condition of the walkways, facilities, and personal safety while using the sidewalk, options for some improvement of the walkways, and community experience as pedestrian. The results of this study shows that most respondents age are between 18-27 years old, 91.9% respondents were using the walkways, the most mode of transportation is car and followed by walking, the origin and destination that most frequently used by UMP communities are from Bus Stop to Blok W, Residential College 3 to Etim Building and Cafeteria 3 to Cariff Building because it is the main route to go to the classes, office, cafeteria and mosque. For male respondents either staffs or students, they usually used the walkway to go to the mosque and cafeteria more than female respondents who daily used for class and college, the respondents majority used walkways 2 to 4 times per day. Then, a majority respondent wants to upgrading the walkways by replacement of roof and adding more lighting. In conclusion, this study shows that pedestrian within UMP Campus really need improvement for walkways especially for the female students who always used the walkways.